A CONTRIBUTION TO PASSIVE SHOCK ABSORBER FORCE INVESTIGATION - Demić, Miroslav D.; Belingardi, Giovanni; Diligenski, Đorđe (Journal of Applied Engineering Science, 2014)
Shock absorbers are fundamental part of the vehicle suspension. Suspensions are needed to guarantee vehicle handling and passenger riding comfort. For good handling and braking performance of the vehicle, the tire-road contact forces need to be as stable as possible. Each wheel should always remain in contact with the ground. Comfort means that vibrations, induced by road profile during riding, are of a minimal nuisance to the passengers. When designing a new vehicle, a lot of development effort is focused on the optimal choice of the suspension parameters, stiffness and damping.This paper presents some results of an experimental study conducted on three shock absorbers types that are in current production at Magneti-Marelli. Experimental tests were performed in conditions of random excitation. The aim of this study, based on the experimental data and by use of statistical methods, was to investigate which of the kinematic parameters of excitation has the major impact on damping force of shock absorber (displacement, velocity or acceleration).
Keywords: Ride comfort; Passive shock absorber; Vehicle